A1 8 Boiling Water With a Hair Dryer - Tang, Cheuk; Armitage, Lewis; Alexander, Matthew (Physics Special Topics, 2023)
We investigate if it would be possible to boil water from room temperature with a hair dryer, and the time taken to do this. We also explore the energy transfers associated with this. We conclude that it is possible to do this, taking a time of 235 seconds.